Low Cost Ergonomics Solution for Safe Work Posture at Conventional Milling Machine: A Case Study - Halim, I.; Radin Umar, R.Z.; Syed Mohamed, M.S.; Jamli, M.R; Ahmad, N.; Pieter, H.H.I (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Conventional milling machine has been recognized as one of the solutions for high productivity and economical machining processes. However, the existing design of conventional milling workstation leads to non-neutral work postures because of the machine operator has to bend downward his torso for better visualization in setting and machining the workpiece. The aim of this study is to redesign the existing milling workstation by focusing on operator’s visualization and work posture. This study applied Rapid Upper Limb Assessment (RULA) to assess the work posture of the operator while performing milling operation. The existing milling workstation was redesigned by attaching a low cost LED light and a magnifying glass to improve operator’s visualization in setting and machining the workpiece. Results of work posture analysis revealed that RULA score reduced from 7 to 3 due to application of these tools. This study concluded that low cost intervention is meaningful in improving work postures of conventional milling machine operators.